Evaluation of weight change and hypoglycaemia as mediators in the association between insulin use and death. Issue 12 (29th August 2019) - Min, Jea Young; Hackstadt, Amber J.; Griffin, Marie R.; Greevy Jr, Robert A.; Chipman, Jonathan; Grijalva, Carlos G.; Hung, Adriana M.; Roumie, Christianne L.
Abstract: Aim: To evaluate whether weight change or hypoglycaemia mediates the association between insulin use and death. Materials and Methods: In a retrospective cohort of veterans who filled a new prescription for metformin and added insulin or sulphonylurea (2001‐2012), we assessed change in body mass index (BMI) and hypoglycaemia during the first 12 months of treatment intensification. Cox proportional hazards models compared the risk of death between treatment groups. Using the difference method, we estimated the indirect effect and proportion mediated through each mediator. A sensitivity analysis assessed mediators in the first 6 months of intensified therapy. Results: Among 28 892 patients surviving 12 months, deaths per 1000 person‐years were 15.4 for insulin users and 12.9 for sulphonylurea users (HR 1.20, 95% CI 0.87, 1.64). Change in BMI and hypoglycaemia mediated 13% (−98, 98) and −1% (−37, 71) of this association, respectively. Among 30 214 patients surviving 6 months, deaths per 1000 person‐years were 34.8 for insulin users and 21.3 for sulphonylurea users (HR 1.66, 95% CI 1.28, 2.15). Change in BMI and hypoglycaemia mediated 9% (1, 23) and 0% (−9, 4) of this association, respectively. Conclusions: We observed an increased risk of death among metformin users intensifying treatment with insulin versus sulphonylurea and surviving 6 months of intensified therapy, but not among those surviving 12 months. This association was mediated in part by weight change.